情真？情貞：論馮夢龍在《三言》中的情愛觀: Is Authentic Love or Chastity? The Nature of Feng Menglong’s Discourse on "Teaching of Qing (Love)” in His Sanyan Collections
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">這篇論文分析馮夢龍《三言》故事中有關貞節與情愛的書寫，以討論明末江南士人圈中，對家庭倫理與“情教”的理解與宣揚。“情教”觀念於十七世紀被馮夢龍正式提出，並通過白話小説與戲曲深入人心。《三言》中的情愛書寫，提供了城市士紳讀者（包括婦女）對才子佳人式的婚姻的期待。一般學者多視馮夢龍爲陽明心學與反道學的李贄的追隨者，本文則認爲，馮夢龍爲程朱理學與“情教”提供了一個接合點。李贄並不反對真道學與禮義，更爲節婦作傳，强調“理即禮也”；馮夢龍也在《情史》序言中明確指出，“六經皆以情教也”。程朱理學視“夫婦”一倫與家庭爲中國社會的基石，馮氏因而通過白話文學的影響力，倡議五倫乃根源於“情”，而“情”則必須以五倫的維繫與實踐爲依歸。這篇論文因此分爲兩部分：第一部分爲文本分析，探討《三言》中的貞節與愛情；第二部分則簡要討論《三言》中失意文人亟於移風易俗的心理焦慮，以及所反映出的晚明思潮與社會史。 This paper analyzes the motif of chaste romance in Feng Menglong’s Sanyan collections — Yushi mingyan, Jinshi tungyan, and Xinshi henyan — to demonstrate the intersection of Confucian ethics and the Teaching of Qing (feelings). Many scholars argue that romance in vernacular literature like Sanyan collections reflects the call of human feelings away from Confucian morality. Feng, for them, stands opposite to the inflexible ideology of the Learning of the Way, devoting to the liberation of love from gender segregation and detailing the concept of the Teaching of Qing. However, Feng intended to bridge the gap between the Learning of the Way and the Teaching of Qing by addressing that, “The Six Classics all attempt to teach through qing." He conformed to Confucian ethics that “husband-wife” the most important relationship and family were the cornerstone of a society, while making a revision that ‘qing’ be the drive for five relationships. Feng upheld family, whereas he popularized the intellectual renovation about individualism — the Learning of the Mind and the Teaching of Qing, Feng highlighted traditional women’s virtues and mocked their loss of chastity in trysts, whereas he appreciated women’s authentic feelings toward love. Feng never gave up the didactic tone and emphasized more women’s loyalty to their husband. This paper includes two main sections to argue that Feng, a frustrated Confucian moralist, revealed the traditional tone on women while building the ideal of companion marriage. First, a textual analysis explores the motif of chaste romance by discussing its four types of Sanyan stories. Second, it discusses neo-Confucianism as well as the Teaching of Qing, and their intersection in the late Ming vernacular literature. To conclude, women are not subjects independent from families and husbands to practice alone the individualistic Teaching of Qing. , journal=人文中國學報, author=張嘉蘭, year=2005, month=Aug., pages=511–538